Desentralisasi dan Kapasitas Pemerintah dalam Pembangunan Sumber Daya Manusia di Indonesia - Mohamad Nurfajar Kapriaji; Siswidiyanto, Siswidiyanto (Jurnal Ilmiah Administrasi Publik, 2022)
This paper examines relationship between decentralization and human resourcedevelopment through the intermediary of government capacity that determines thesuccess of development after decentralization. The results of the study show thatdecentralization has been implemented well but there are side effects in the form ofmoney politics and dynasties in political decentralization, the lack of regions thatachieve independence in fiscal decentralization, and the low quality of employeesdue to employee recruitment that is still not optimal in administrativedecentralization. The capacity of the national government is only the capacity ofdistributive and horizontal cooperation that can be categorized as good, the capacityof the local government is only the capacity of horizontal cooperation within onelocal government which is included in the good category. Of the 5 models produced,4 (four) models show the condition of government capacity in the form of outputsand outcomes that can improve human resource development, while the other 1(one) model shows the opposite condition.